Epstein‐Barr virus antibody titer and its association with the domain scores from the World Health Organization's Quality of Life questionnaire: Findings from Rural Hainan Province, China. Issue 1 (11th December 2013) - Inoue, Yosuke; Yazawa, Aki; Li, Dandan; Du, Jianwei; Jin, Yuming; Chen, Yan; Watanabe, Chiho; Umezaki, Masahiro
Abstract : Objective: Epstein‐Barr virus (EBV) antibody titer has recently been used as a biomarker of psychological stress. This is the first study to investigate the association between EBV antibody titer and perceived quality of life (QOL) in Hainan Island, China. Methods: Participants from two regions of Hainan Island, recruited into a larger study investigating the health impact of rapid economic development among rural residents, were stratified by age, sex, and region; 15 people were randomly selected from each of the 16 subgroups, to give a total sample size of 240. EBV antibody titer in dried blood spot samples was measured by enzyme‐linked immunosorbent assay. The abbreviated version of the World Health Organization's Quality of Life questionnaire was used to gather information on six categories of QOL. Multiple linear regression analysis was used to examine the relationship between EBV antibody titer and QOL. Results: After adjusting for the effects of age, sex, region and C‐reactive protein concentration, EBV antibody titer was negatively associated with the physical ( P  = 0.044) and psychological QOL domains ( P  = 0.039). Conclusion: This study suggests that among individuals living in an environment in the initial stages of economic development EBV antibody titer, a biomarker of psychological stress, is not only associated with the psychological aspects of QOL but is also linked to physical problems. Am. J. Hum. Biol. 26:51–55, 2014. © 2013 Wiley Periodicals, Inc.